2017
DOI: 10.1021/acs.chemmater.7b01705
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Synthesis of Widely Tunable Formamidinium Lead Halide Perovskite Nanocrystals

Abstract: Colloidal perovskite nanocrystals based on formamidinium lead halide (FAPbX 3 ) have been synthesized by the ligand-assisted reprecipitation method using PbX 2 − dimethyl sulfoxide complexes as precursors at room temperature. Well-defined cubic-shaped FAPbX 3 nanocrystals have been obtained with a size d of ∼10 nm. The synthesized FAPbX 3 nanocrystals show bright photoluminescence with a high photoluminescence quantum yield (75% for FAPbBr 3 ). The lifetimes of FAPbBr 3 nanocrystals were measured for the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 52 publications
6
97
0
Order By: Relevance
“…Finally, the composite films were irradiated one more time with UV for seconds to complete photopolymerization. X‐ray diffraction (XRD) diffraction patterns of the composite films well consistent with those in our previous report on FAPbBr 3 nanoparticle synthesis (Figure S4, Supporting Information) . The size of FAPbBr 3 nanoparticles in the composite films was dependent on the polymers.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Finally, the composite films were irradiated one more time with UV for seconds to complete photopolymerization. X‐ray diffraction (XRD) diffraction patterns of the composite films well consistent with those in our previous report on FAPbBr 3 nanoparticle synthesis (Figure S4, Supporting Information) . The size of FAPbBr 3 nanoparticles in the composite films was dependent on the polymers.…”
Section: Methodssupporting
confidence: 86%
“…Our approach utilizes the in situ synthesis of perovskite nanoparticles in polymer films during the photopolymerization. Previously, we have demonstrated that formamidinium lead halide (FAPbX 3 ) perovskite nanoparticles can be synthesized from the mixture of PbX 2 ‐DMSO and formamidinium halide (FAX) by decreasing solvent power from dimethylformamide (DMF) to toluene at room temperature . The similar solvent power change can be achieved when polar monomers are polymerized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena are in accordance to previous reports with such asymmetric ligand ratio. [ 32,33 ] Radiative and non‐radiative rates are calculated from PL QY and PL decay time, shown in Table S1, Supporting Information. [ 16 ] All the samples have the similar radiative rate, but along with the ligand amount decrease, non‐radiative rate goes down.…”
Section: Resultsmentioning
confidence: 99%
“…The OM image under a light field is shown in Figure S5 (Supporting Information). The atomic force microscope (AFM) characterization (Figure e) reveals typical thickness of the FAPbBr 3 NP to be ≈12 nm, this is in good consistence with previous reports on FAPbBr 3 NCs (530 nm PL, ≈12 nm in size) …”
Section: Resultsmentioning
confidence: 99%